Refugee Children’s Perspectives on Participating in Music Therapy: A Qualitative Study - Enge, Kaja Elise; Stige, Brynjulf; Nordanger, Dag Øystein (Voices: A World Forum for Music Therapy, 2024)
The health and development of refugee children can be significantly impacted by adverse experiences and prolonged stress. Although previous research and practice have demonstrated the potential benefits of music therapy for children in this situation, there is a lack of research focusing on the perspectives of refugee children themselves. This study aims to explore the participation of refugee children in music therapy within a Norwegian primary school context. The empirical material was collected through semistructured interviews conducted with seven refugee children (aged 8–12) who had been resettled in Norway. Thematic analysis was employed to analyse the interview transcripts. The analysis resulted in three main themes: Accessing Musical Development, which illuminates how music therapy provided opportunities for musical learning with emphasis on socially relevant music; Appropriating Music Therapy as a Social Resource, which illustrates how music therapy sessions facilitated connection with peers; and Experiencing States of Wellbeing which focuses on the children’s descriptions of emotional changes and fun. Findings are discussed in the context of situated learning theory and the impact of adverse experiences on children’s affect regulation capacity. Additionally, the discussion includes reflections on how music therapy can provide resources for regulating affect.